Endograft type and anesthesia mode are associated with mortality of endovascular aneurysm repair for ruptured abdominal aortic aneurysms. (April 2021) - Bellamkonda, Kirthi S; Yousef, Sameh; Zhang, Yawei; Dardik, Alan; Geirsson, Arnar; Chaar, Cassius I Ochoa
Objective: Endovascular aneurysm repair has become the primary treatment modality for ruptured infrarenal abdominal aortic aneurysm. This study examines the impact of endograft type on perioperative outcomes for ruptured infrarenal abdominal aortic aneurysm. Method: The targeted endovascular aneurysm repair files of the American College of Surgeons National Surgical Quality Improvement Program database (2012–2017) were used. Only patients treated for ruptured infrarenal abdominal aortic aneurysm were included. All patients requiring concomitant stenting of the visceral arteries or aneurysmal iliac arteries or open abdominal surgery were excluded. The characteristics of patients treated with the different endografts and the corresponding outcomes were compared using Stata software. Results: There were 479 patients treated with the three most common endografts: Cook Zenith ( n  = 127), Gore Excluder ( n  = 239), and Medtronic Endurant ( n  = 113). The number of other endografts was too small for statistical analysis. Compared to patients treated with Excluder or Endurant, the patients treated with Zenith had significantly lower body mass index ( P  < .001) and were less likely to be white ( P  < .001). On the other hand, patients treated with Endurant were less likely to be smoker ( P  = .016). Patients treated with Zenith had significantly larger ruptured infrarenal abdominal aortic aneurysm diameter ( P  = .045). The overall mortality was 18% and morbidity 74.3%. There was a statistically significant difference in overall mortality (Zenith = 11.8%, Excluder = 18%, Endurant = 24.8%, P  = .033) but not morbidity ( P  = .808) between the three groups. Post hoc analysis for overall mortality showed only significant difference between Zenith and Endurant. The difference in mortality was not significant in patients presenting with ruptured infrarenal abdominal aortic aneurysm without hypotension ( P  = .065). On multivariable analysis, treatment with the Endurant endograft was associated with increased mortality compared to Zenith (odds ratio = 3.0 [confidence interval 1.31–6.7]). General anesthesia (odds ratio = 2.67 [confidence interval 1.02–7.02]), rupture with hypotension (odds ratio = 4.49 [confidence interval 2.54–7.95]), and dependent functional status (odds ratio = 5.7 [confidence interval 1.96–16.59]) were independently associated with increased mortality while increasing body mass index (odds ratio = 0.97 [confidence interval 0.95–0.99]) was associated with reduced risk of mortality. Conclusions: This study highlights contemporary outcomes of endovascular aneurysm repair for ruptured infrarenal abdominal aortic aneurysm with relatively low mortality. Endograft type and anesthesia technique are modifiable factors that can potentially improve outcomes. Significant variation in the outcomes of the different endografts warrants further research.